벼 중생 내병 다수성 신품종 “눈보라” - 하기용(Ki-Yong Ha); 고재권(Jae-Kwon Ko); 김기영(Ki-Yeong Kim); 남정권(Jeong-Kwon Nam); 고종철(Jong-Cheol Ko); 김보경(Bo-Kyeong Kim); 백만기(Man-Kee Baek); 정진일(Jin-Il Cheong); 백소현(So-Hyeon Baek); 김정곤(Chung-Kon Kim) (Korean journal of breeding, 2008)
“unbora”is a new japonica rice cultivar developed from a cross between Iksan433 resistant to bacterial blight and Miyadamamochi, a waxy line. at Honam Agricultural Research Institute, NICS, RDA, in 2006. This cultivar is a short grain shape and about 118 days of growth duration from transplanting “unbora”to harvesting under Korean climatic conditions. The milled rice are snow white and glutinuous. This cultivar shows high resistant reactions to the bacterial blight pathogen race K1～K3 and blast respectively. The milled rice yield of “unbora”is about 5.34 MT/ha under the standard fertilizer level of the ordinary transplanting cultivation. “unbora”would be adaptable for in the middle plain, north middle-mountin plain and Honam plain, and Youngnam plain areas of Korea.